Revisiting the safety of intraoperative cell salvage in cancer surgery: how to evaluate the functional properties of remaining cancer cells - Sureshkumar, Harini K.; Schenz, Judith; Waters, Jonathan H.; Weigand, Markus A.; Seyfried, Timo; Juratli, Mazen A.; Frietsch, Thomas; Fischer, Dania (European journal of surgical oncology, 2025)
Cancer surgery accounts for a substantial proportion of allogeneic blood use. As demographic changes lead to a growing number of oncologic procedures, transfusion demands are increasing, while blood supply shortages persist. Moreover, allogeneic blood transfusions carry inherent risks, especially in cancer patients, due to potential transfusion-associated immunomodulatory effects. Intraoperative cell salvage (IOCS) potentially presents a promising strategy to reduce allogeneic transfusions. However, its application in oncologic surgery remains controversial due to the theoretical risk of reinfusing viable tumor cells. Techniques to mitigate this risk include the use of leukocyte depletion filters, irradiation, and antibody-based treatments. Nonetheless, the exact oncologic burden of salvaged blood, in terms of tumor cell quantity, viability, proliferative capacity, migratory behavior, and metastatic potential, remains insufficiently characterized. Meta-analyses of observational studies suggest that oncologic outcomes in patients treated with IOCS are comparable to or better than those of patients treated with allogeneic blood transfusions. Yet, randomized controlled trials have not been performed yet due to missing preclinical evidence. This review aims to summarize the current evidence on the biology of remaining tumor cells in salvaged blood, evaluate the effectiveness of existing cell reduction strategies, and highlight key methodological challenges in quantifying and characterizing residual malignant cells. In addition, we spotlight recent advances in laboratory assays designed to detect circulating tumor cells (CTCs) in blood, particularly technologies developed for the analysis of intravascular CTCs. Given their similar methodological principles, these technologies offer promising tools for future safety assessments of IOCS in oncologic surgery.
Online verfügbar: 22. Oktober 2025, Artikelversion: 25. Oktober 2025
Gesehen am 01.12.2025